Transgressão e salvaguarda: olhares sobre a pixação e as edificações históricas do bairro de Jaraguá - Maceió/AL - Pessoa, Eloisa Lemos (2020)
This work consists of a study focused on pixação in the city of Maceió, especially those found in the historical district of Jaraguá. The district is configured as one of the first formation nuclei of the city of Maceió and, therefore, presents institutionally preserved historical elements.However, like most Brazilian historical centers, Jaraguá is surrounded by several conflicts that involve the way buildings and monuments are preserved, the choice of heritage goods and a long process of social segregation and commodification of space. In the midst of this scenario, pixações are carried out on the walls, gates and other surfaces of the neighborhood, in disregard of what the hegemonic power considers ideal and pleasant. In view of this, there is an interest in seeking to understand how pixação is inserted in the landscape of Jaraguá, especially around Rua Sá e Albuquerque. In order to do so, it was necessary to survey how Brazilian cultural heritage was built and the laws that govern it, as well as the heritage assets of the State and the municipality, understanding the profile of what is considered heritage; a physical analysis and the dynamics of occupation of the study cutout, paying attention to the way its landscape has been shaped over the years; as well as a contextualization about pixação in Maceió, reflecting on some characteristics of the local movement. Finally, I reflect on the physical, social and political contexts that involve pixação in the landscape of the Jaraguá neighborhood, considering its political, questioning, inclusive and resignifying potential of urban space.